(untitled) (Biocenosis, 2015)
This is the first study that investigated the perceptions of herbalists in public markets in the city of Juazeiro do Norte, Brazil. Through the results we analyze the socio-environmental context they are embedded. We have seen that despite the conservation policies, this practice still remains from one generation to another.